Development and characterization of alginate/pectin edible films containing Lactobacillus plantarum KMC 45 - Shahrampour, Dina; Khomeiri, Morteza; Razavi, Seyed Mohammad Ali; Kashiri, Mahboobeh (Food science & technology, 2020)
The incorporation of probiotic cells in thin-layer edible films is a new strategy for development of functional foods. In this study, the effect of plasticizers type (glycerol and sorbitol) along with their concentration (40, 50 and 60% w/w polymer) and alginate/pectin ratio (100:0, 75:25, 50:50, 25:75 and 0:100) on the survival of Lactobacillus plantarum KMC45 during the drying process and storage of films at 25 °C and 4 °C were investigated. The results demonstrated that the highest survival of L. plantarum KMC45 was obtained in the films containing the highest proportion of alginate and sorbitol (60% w/w polymer) at 4 °C during 30 days. Also, the immobilization of probiotic cells in films decreased their water vapor permeability (WVP) and had no significant impact on thickness, aw, water solubility and color parameters of films. The results suggested that alginate/pectin-based edible films could be employed as suitable carrier systems for probiotic bacteria, especially at refrigeration temperatures. •The biopolymer and plasticizer type affect L. plantarum KMC45 viability in films.•The increase of sorbitol concentration improved L. plantarum KMC45 survival during film drying.•The increase of alginate to pectin ratio enhanced L. plantarum KMC45 viability in composite films.•The 4 °C was better than 25 °C for probiotic film storage.•The incorporation of L. plantarum KMC45 in alginate/pectin films changed their characteristics such as WVP.